Hepatocyte Turnover in Chronic HCV-Induced Liver Injury and Cirrhosis - Nikolaos P. Karidis; Ioanna Delladetsima; Stamatios Theocharis (Gastroenterology Research and Practice)
Chronic hepatitis C virus (HCV) infection may eventually lead to progressive liver fibrosis and cirrhosis through a complex, multistep process involving hepatocyte death and regeneration. Despite common pathogenetic pathways present in all forms of liver cirrhosis irrespective of etiology, hepatocyte turnover and related molecular events in HCV-induced cirrhosis are increasingly being distinguished from even “similar” causes, such as hepatitis B virus- (HBV-) related cirrhosis. New insights in HCV-induced hepatocellular injury, differential gene expression, and regenerative pathways have recently revealed a different pattern of progression to irreversible parenchymal liver damage. A shift to the significant role of the host immune response rather than the direct effect of HCV on hepatocytes and the imbalance between antiapoptotic and proapoptotic signals have been investigated in several studies but need to be further elucidated. The present review aims to comprehensively summarize the current evidence on HCV-induced hepatocellular turnover with a view to outline the significant trends of ongoing research.